UZBEKISTAN-GERMANY: A NEW STAGE OF COOPERATION IN THE FIELD OF MEDICINE - Umarova Ra’nogul Olim qizi; Tog’ayeva Nurdida Ortiq qizi; Namozova Umida Abdurafiq qizi; Ravshanova Kumushbibi Qobil qizi (Reviews of Modern Science, 2022)
After backup Soviet Union founded new countries old them regions. Also, unified two German countries in Europe. Such as arose new independence states, one of them Republic of Uzbekistan, other was Federative Republic of Germany in Eurasia region. This are states established diplomatic relations at short time. Bilateral relations are rising during independence’s years. Uzbekistan and Germany are reliable partners on today. In this article showed a new stage of cooperation in the field of medicine of Uzbekistan and Germany on the context of globalization by authors.